Draft Annual Plan 1986-87 Punjab - Planning Commission (Planning Commission, 1986)
Agriculture is the backbone of the State’s economy. Progress in Agriculture, thus, holds the key to rapid economic development of the State having predominantly an agricultural economy and where about 80 per cent of the population depends directly or indirectly on agriculture. Punjab achieved a major break—through in agricultural production, especially in the production of wheat and rice as a result of which the State is the largest single contributor to the Central rice and wheat pool.
Planning Department Punjab